Evaluating SEA modelling of lightweight building elements containing cross laminated timber - Augustsson, Tobias (My University, 2016)
To create a future sustainable environment more environmentally friendly building materials must be included in the building process. The use of timber is becoming more common when constructing larger dwellings. One of the challenges when using timber constructions is predicting the sound insulation. This thesis is a part of the project Silent Timber Build and aims to investigate the possibility of using statistical energy analysis (SEA) to predict sound insulation in timber buildings. The focus lies on a timber construction called cross laminated timber (CLT). SEA software has been developed by the French company,and Silent Timber Build partner, InterAC. This software, called SEAWOOD, is used to model the constructions investigated in this thesis. To get a better understanding of how the software operates, a simplified SEA model of a CLT plate is made in Matlab. To validate the SEA models the calculated reduction index curves are compared to lab measurements. These comparisons show that it is possible to model simpler timber constructions in SEA with reasonable accuracy. More complicated constructions may need more work to be properly modelled. Limitations in the SEA model makes it unsuitable for investigating the lower frequency region and other methods should be used to get more reliable results in this region.
Keywords: Building Futures; Akustik; Building Futures; Acoustics